Respuesta :

The simplification of each form of expression is;

  • (6r + 7) + (13 + 7r) = 13r + 20
  • (13 - 3/2r) - (1 - r) = 12 - 1/2r
  • (-8 - r) + (2r - 4) = -12 + r
  • (7r - 3/2) - (2/3 + 6r) = r - 13/6

Simplification

(6r + 7) + (13 + 7r)

= 6r + 7 + 13 + 7r

= 13r + 20

(13 - 3/2r) - (1 - r)

= 13 - 3/2r - 1 + r

= 12 - 3/2r + r

= 12 -3r+2r/ 2

= 12 - 1/2r

(-8 - r) + (2r - 4)

= -8 - r + 2r - 4

= -12 + r

(7r - 3/2) - (2/3 + 6r)

= 7r - 3/2 - 2/3 - 6r

= r -9-4/6

= r - 13/6

Learn more about simplification:

https://brainly.com/question/723406

#SPJ1